Legenda makam keramat gunung batu sebagai sistem mitigasi bencana di Sesar Lembang - Harini, Yostiani Noor Asmi; Cambara, Hegar Krisna; Kusumawardhana, Gelar Taufiq (Jurnal Pendidikan Bahasa dan Sastra, 2021)
A legend is a folk story whose events are considered to have really happened. The characters in the story are believed to have lived in the past and the places where the events occurred can be referred to in real life. Events, characters, and places considered important by the community will be immortalized by the community to become legends. Those legends are told by people from generation to generation to deliver the knowledge they have. Related to that, this research was motivated by the existence of sacred tomb on Mount Batu, Lembang District, West Bandung Regency. The story about Mount Batu sacred tomb is believed by the local community as a legend. This research described the narrative structure of the legend, the context of the story, and the function of the legend for the native through the perspective of folklore. The results of the study show that the legend of Mount Batu sacred tomb is closely related to the knowledge system of the community, especially regarding the disaster mitigation system. The legend was delivered from generation to generation to warn the surrounding community about the threatening disaster in the area which is included in the Lembang Fault area.